The insulin-like growth factor system is modulated by exercise in breast cancer survivors: a systematic review and meta-analysis - Meneses-Echávez, José Francisco (BMC Cancer, 2016)
BACKGROUND: Insulin-like growth factors (IGF´s) play a crucial role in controlling cancer cell proliferation, differentiation and apoptosis. Exercise has been postulated as an effective intervention in improving cancer-related outcomes and survival, although its effects on IGF´s are not well understood. This meta-analysis aimed to determine the effects of exercise in modulating IGF´s system in breast cancer survivors. METHODS: Databases of PuMed, EMBASE, Cochrane Central Register of Controlled Trials, EMBASE, ClinicalTrials.gov, SPORTDiscus, LILACS and Scopus were systematically searched up to November 2014. Effect estimates were calculated through a random-effects model of meta-analysis according to the DerSimonian and Laird method. Heterogeneity was evaluated with the I(2) test. Risk of bias and methodological quality were evaluated using the PEDro score. RESULTS: Five randomized controlled trials (n = 235) were included. Most women were post-menopausal. High-quality and low risk of bias were found (mean PEDro score = 6.2 ± 1). Exercise resulted in significant improvements on IGF-I, IGF-II, IGFBP-I, IGFBP-3, Insulin and Insulin resistance (P < 0.05). Non-significant differences were found for Glucose. Aerobic exercise improved IGF-I, IGFBP-3 and Insulin. No evidence of publication bias was detected by Egger´s test (p = 0.12). CONCLUSIONS: Exercise improved IGF´s in breast cancer survivors. These findings provide novel insight regarding the molecular effects of exercise on tumoral microenvironment, apoptosis and survival in breast cancer survivors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-016-2733-z) contains supplementary material, which is available to authorized users.